2010
DOI: 10.1016/j.immuni.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via the MyD88 Adaptor Protein in B Cells Suppresses Protective Immunity during Salmonella typhimurium Infection

Abstract: The myeloid differentiation primary response gene 88 (Myd88) is critical for protection against pathogens. However, we demonstrate here that MyD88 expression in B cells inhibits resistance of mice to Salmonella typhimurium infection. Selective deficiency of Myd88 in B cells improved control of bacterial replication and prolonged survival of the infected mice. The B cell-mediated suppressive pathway was even more striking after secondary challenge. Upon vaccination, mice lacking Myd88 in B cells became complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
282
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(290 citation statements)
references
References 59 publications
7
282
1
Order By: Relevance
“…It is tempting to speculate that MZB may prime CD4 T cells with a regulatory phenotype during the very early stages of infection, which then contribute to suppress protective Th1 responses. A recent study has shown that signaling via MyD88 in B cells suppresses NK cells and T cell responses in Salmonella typhimurium-infected mice (56). In this study, IL-10 was an essential mediator of the B cell inhibitory effects on NK and T cells, and MyD88 was crucial for mediating these effects.…”
Section: Discussionmentioning
confidence: 60%
“…It is tempting to speculate that MZB may prime CD4 T cells with a regulatory phenotype during the very early stages of infection, which then contribute to suppress protective Th1 responses. A recent study has shown that signaling via MyD88 in B cells suppresses NK cells and T cell responses in Salmonella typhimurium-infected mice (56). In this study, IL-10 was an essential mediator of the B cell inhibitory effects on NK and T cells, and MyD88 was crucial for mediating these effects.…”
Section: Discussionmentioning
confidence: 60%
“…Notably, TLRinduced B cell-derived IL-10 production interferes with Ag presentation and T cell activation in a Salmonella infection model (54). Well in line with these findings T cell hyporesponsiveness was recently described in a murine model for chronically persistent S. aureus infection (71), although the exact mechanism promoting T cell anergy remained obscure.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, IL-10-secreting B cells have been identified as important negative regulators in immunity to infection (54). Intrigued by these reports we wanted to know whether SpA-mediated B cell activation could selectively trigger the expansion of this regulatory B cell subset.…”
Section: Cooperation Of Pdc and B Cells Supports Il-10 Productionmentioning
confidence: 99%
“…mTORC1 is a protein complex that is involved in metabolism and autophagy regulation, and the latter is an important process that enables intracellular bacterial control; therefore, through Akt activation and IL-10 production, Salmonella might regulate autophagy to avoid control by the host. It has been reported that B cells produce IL-10 in response to Salmonella infection [57]. Thus, it is likely that through autocrine mechanisms, IL-10 also contributes to bacterial survival by blocking xenophagy.…”
Section: Discussionmentioning
confidence: 99%